Hardware Implementation of Solar based Boost to SEPIC Converter Fed Nine Level Inverter System - D. Jasmine; M. Gopinath (Institute of Advanced Engineering and Science, 2016)
Multi level inverters are widely used in high power applications because of low harmonic distortion. This paper deals with the simulation and implementation of PV based boost to SEPIC converter with multilevel inverter. The output of PV system is stepped up using boost to sepic converter and it is converted into AC using a multilevel inverter. The simulation and experimental results with the R load is presented in this paper. The FFT analysis is done and the THD values are compared. Boost to SEPIC converter is proposed to step up the voltage to the required value. The experimental results are compared with the simulation results. The results indicate that nine level inverter system has better performance than seven level inverter system.